STRATEGI PENINGKATAN KESEJAHTERAAN GURU MELALUI KOMPENSASI DI LEMBAGA PENDIDIKAN ISLAM - Ambarawadi, Ndanda; Maunah, Binti; Junaris, Imam (Jurnal Manajemen Pendidikan, 2025)
Teacher welfare is one of the key factors in improving the quality of education in Islamic educational institutions. However, there are still many teachers who face welfare challenges due to the suboptimal compensation system, both financially and non-financially. This study aims to analyze strategies to improve teachers' welfare through the provision of fair compensation and in accordance with Islamic principles. The research method used is a literature study by examining various literature, journal articles, and the results of previous research related to teacher compensation and welfare in Islamic educational institutions. The results of the study show that effective compensation is not only in the form of salaries and benefits, but also includes non-financial rewards such as training, career development, a conducive work environment, and recognition of teachers' dedication. The integration of Islamic values in the compensation system, such as the principles of fairness, transparency, and proportionality, has been proven to increase teacher motivation, loyalty, and professionalism. In addition, the main challenges faced by Islamic educational institutions in the implementation of compensation are budget limitations and the performance appraisal system is not optimal. Therefore, it is necessary to innovate sustainable compensation strategies, such as the use of alternative sources of funds, periodic evaluations, and the involvement of teachers in the formulation of compensation policies.